Potential of wild plant Artemisia judaica L. as sustainable source of antioxidant and antimicrobial compounds - El-Amier, Yasser A.; Al Borki, Abd El-Nasser S.; Elagami, Shrouk A. (Journal of Experimental Sciences, 2019)
Artemisia judaica L. (Shih Balady, family Asteraceae), is a medicinal plant that grows in the desert, commonly used as tea by population in Egypt Sinai and of Saudi Arabia. The present study aims to evaluate antimicrobial and antioxidant activities of aerial parts of A. judaica collected from the inland desert (Wadi Hagoul) of Egypt. Total phenolics, tannins, alkaloids, flavonoids, and saponins were measured in the plant of interest. According to the reduction of DPPH the anti-oxidant activity was measured. Different extracts of A. judaica were screened for their antimicrobial activity against nine pathogenic microorganisms using filter paper disc assay. The secondary metabolites of A. judaica were examined and proved that it was rich in tannins and phenolics (13.29 and 7.62 mg/g dw). The IC50 values of A. judaica extract was 1.78 mg.ml-1 compared to standard catechol (0.15 mg.ml-1). In the present study, the extracts of A. judaica showed unusual activity depending on the type of bacteria and fungi. Also, ethyl acetate and methyl alcohol extracts showed considerable broad spectrum (77.78%, each) against both bacteria and fungi, followed by acetone, then methylene chloride and petroleum ether extracts. This study showed that A. judaica extracts could be used as antimicrobial substances in pharmaceutical and food preservation systems.